Genome-wide identification and analysis of expression of pathogenesis-related protein 1 (PR-1) gene family in brown algae - Teng, Linhong; Liang, Shuxia; Chen, Jiayi; Kobe, Bostjan; Ye, Naihao; Wang, Hui; Song, Jian (Frontiers in Plant Science, 2026)
The pathogen-related protein 1 (PR-1) family plays an important role in plant response to biotic and abiotic stresses. PR-1 proteins have been studied in many plant species; however, they were not systematically studied in brown algae, which are important components of coastal ecosystems and have great economic value in the aquaculture industry. In the present study, we characterized the structure, evolution and expression of PR-1 proteins in brown algal genomes. A total of 141 PR-1s were identified in the 19 brown algal genomes, with an average of 7 genes in each species. Most PR-1s are acidic, while only 18 PR-1s are basic. Phylogenetic analysis showed that PR-1s in brown algae clustered into five clades, and showed no strong relationship with other lineages, suggesting an ancient origin. All the PR-1s contain a conserved CAP superfamily domain. Some PR-1s contain distinct functional domains, such as the WSC, Blect, and Bulb-type lectin domains, which are involved in carbohydrate binding. Their promoter regions were enriched in stress-response elements, hormone-response elements, growth and development elements. GO and KEGG annotation showed that brown algal PR-1 proteins may be involved in diverse roles and pathways. Moreover, expression analysis shows that some PR-1s, especially basic proteins are responsive to abiotic stress conditions and life stage development, further suggesting they participate in multiple functional pathways. Our results provide important data for future research on the function of brown algal PR-1 family genes.